Reproduction and optical analysis of Morpho-inspired polymeric nanostructures. (11th May 2016) - Tippets, Cary A; Fu, Yulan; Jackson, Anne-Martine; Donev, Eugenii U; Lopez, Rene
Abstract: The brilliant blue coloration of the Morpho rhetenor butterfly originates from complex nanostructures found on the surface of its wings. The Morpho butterfly exhibits strong short-wavelength reflection and a unique two-lobe optical signature in the incident ( θ ) and reflected ( ϕ ) angular space. Here, we report the large-area fabrication of a Morpho -like structure and its reproduction in perfluoropolyether. Reflection comparisons of periodic and quasi-random 'polymer butterfly' nanostructures show similar normal-incidence spectra but differ in the angular θ – ϕ dependence. The periodic sample shows strong specular reflection and simple diffraction. However, the quasi-random sample produces a two-lobe angular reflection pattern with minimal specular refection, approximating the real butterfly's optical behavior. Finite-difference time-domain simulations confirm that this pattern results from the quasi-random periodicity and highlights the significance of the inherent randomness in the Morpho 's photonic structure.